An investigation into the viability of deploying thin client technology to support effective learning in a disadvantaged, rural high school setting - Ndwe, Tembalethu Jama (Rhodes University, Faculty of Science, Department of Computer Science, 2002)
Computer Based Training offers many attractive learning opportunities for high school pupils. Its deployment in economically depressed and educationally marginalized rural schools is extremely uncommon due to the high technology skills and costs involved in its deployment and ongoing maintenance. This thesis puts forward thin client technology as a potential solution to the needs of education environments of this kind. A functional business case is developed and evaluated in this thesis, based upon a requirements analysis of media delivery in learning, and upon formal cost/performance models and a deployment field trial. Because of the economic constraints of the envisaged deployment area in rural education, an industrial field trial is used, and the aspects of this trial that can be carried over to the rural school situation have been used to assess performance and cost indicators. Our study finds that thin client technology could be deployed and maintained more cost effectively than conventional fat client solutions in rural schools, that it is capable of supporting the learning elements needed in this deployment area, and that it is able to deliver the predominantly text based applications currently being used in schools. However, we find that technological improvements are needed before future multimediaintensive applications can be adequately supported.
Keywords: Network computers; Education -- Data processing